From kitchen to health: how culinary workshops influence eating habits, autonomy, and wellbeing in adults–A scoping review - da Fonseca, Pâmela Gracielle; Siqueira, Lucas de Carvalho; Raposo, António; Alslamah, Thamer; Albaridi, Najla A.; Saraiva, Ariana; Guimarães, Nathalia Sernizon (Frontiers in Nutrition, 2025)
Inadequate dietary patterns have significantly contributed to the rise of chronic diseases, highlighting the need for effective interventions. Culinary workshops have emerged as a promising strategy by offering practical and interactive food and nutrition education that may enhance food choice autonomy and promote healthier eating behaviors. This scoping review was conducted according to the Joanna Briggs Institute guidelines and the PRISMA-ScR checklist, with a protocol registered in the Open Science Framework. Searches were performed in PubMed, Embase, Cochrane Library, and the Virtual Health Library, including intervention studies published between 2005 and 2025. Study selection and data extraction were independently performed by three reviewers. A total of 30 studies were included, most from the United States (67.6%) and Australia (23.5%), with in-person workshops lasting 4–12 weeks. Improvements were reported in food autonomy, self-efficacy, and culinary practices in 81% of studies. Over 90% reported increased consumption of fruits, vegetables, and whole grains, along with reductions in ultra-processed foods. 15 studies noted improvements in anthropometric parameters, while 14 reported clinical benefits. Quality of life was evaluated in seven studies, with significant improvements in three. Culinary workshops appear to be effective in promoting health, though more standardized studies in diverse populations are warranted.